Os efeitos do 1,25- dihidroxicolecalciferol e vitamina D3 no desempenho e qualidade óssea de frangos de corte - Fernanda Lima de Souza Castro (2016)
This study was conducted to evaluate the effect of two levels of vitamin D3 (cholecalciferol) and the inclusion or not of 1,25- dihydroxycholecalciferol (1,25-(OH)2D3) on live performance and bone quality of broiler chickens. Diets for starter (1 to 21d) and grower (22 to 40d) periods were used ad libitum. A vitamin supplement provided adequate amounts of all vitamins except for vitamin D3. The vitamin D3 levels were: 2.500 and 2.000 UI/kg, for the starter and grower periods, respectively, according to levels commercially used, and 1.250 and 1.000 UI/kg, representing a reduction of 50%. The 1,25-(OH)2D3 source was a commercial product consisting of dried leaves of Solanum glaucophyllum (0,5 g 1,25-(OH)2D3/kg). The experimental design was completely randomized in a 2x2 factorial arrangement. 960 day-old male Cobb®500 broiler chicks were randomly distributed into 32 floor pens, with 30 chicks each. Each treatment was replicated eight times. On day 21 and 40, one broiler per replicate was killed and tibiae and femora were removed. The bones were analyzed through mineral content determination, a biomechanical assay and morphological analysis. No significant differences were found related to vitamin D3 levels and the addition or not of 1,25-(OH)2D3 for live performance, mineral content, strength, stiffness and morphology. Toughness was lower when 1,25-(OH)2D3 was used at 21 days, but this effect did not persist at 40 days of age. The reduction up to 50% of the vitamin D3 levels is sufficient to ensure the performance and bone development of broilers at 21 and 40 days of age. The inclusion of 0,5 g 1,25-(OH)2D3/kg in addition to diets with sufficient levels of vitamin D3 showed no effect on the improvement of live performance and bone quality at 21 and 40 days of age.